Association of Green Tea Consumption with Mortality from All-cause, Cardiovascular Disease and Cancer in a Chinese cohort of men - Liu, Junxiu (Eur J Epidemiol, 2016)
Tea is the most ancient and popular beverage in the world and its beneficial health effects has attracted tremendous attention worldwide. However, the effects of green tea consumption on the risk of mortality from all-cause, cardiovascular disease (CVD) and cancer in epidemiological studies are still scant and inconclusive. We studied male participants free of pre-existing disease status aged 40-79 from the Chinese Prospective Smoke Study, who were followed up for mortality from 1990 until 2006. Green tea consumption and other covariates were assessed by the standardized questionnaire. Cox regression analyses were used to quantify the associations of green tea consumption with all-cause, CVD and cancer mortality. During 15 years of follow-up (mean, 11years; total person-years, 1,961,791), 32,700 men died among the sample size of 164,681. After multivariate adjustment for potential confounders, green tea drinkers as compared with non-green tea drinkers had significantly reduced risk of dying from all-cause, CVD and cancer. The hazard ratios (HRs) for death from all-cause among subjects who drank green tea, as compared with those who did not drink green tea, were as follows: 0.94 (95% CI: 0.89, 0.99) for ≤5 grams/day, 0.95 (0.91, 0.99) for 5-10 grams/day and 0.89 (0.85, 0.93) for >10 grams/day. The HRs for death from CVD and cancer among people who drank green tea, as compared with those who did not drink green tea, were as follows: 0.93 (0.85, 1.01) for ≤5 grams/day, 0.91 (0.85, 0.98) for 5-10 grams/day and 0.86 (0.79, 0.93) for >10 grams/day and 0.86 (0.78, 0.98) for ≤5 grams/day, 0.92 (0.83, 1.00) for 5-10 grams/day and 0.79 (0.71, 0.88) for >10 grams/day, respectively. The patterns of these associations differ by smoking, alcohol drinking and locality. This study suggests that green tea consumption might reduce the risk of death from all-cause, CVD and cancer.